The Influence of Inflation And Economic Growth (GDP) on The Stock Prices of Manufacturing Companies in The Jakarta Islamic Index (JII) - Sari, Indaniaty Hasanah; Tambunan, Khairina; Harahap, Muhammad Ikhsan (Institut Agama Islam Negeri (IAIN) Curup, 2025)
Purpose: This study analyses the impact of inflation, economic growth, and previous stock prices on manufacturing companies’ stock prices in the Jakarta Islamic Index (JII). Understanding macroeconomic factors that influence the Islamic capital market, particularly in the context of stock price volatility, is urgent. Design/Method/Approach: The quantitative research method with multiple linear regression analysis. Secondary data were obtained from the Indonesia Stock Exchange (IDX), the Central Bureau of Statistics (BPS), and other online sources, covering the research period from 2021 to 2023. Data analysis was conducted using the E-Views 10 software. Findings: The research results indicate that inflation does not have a significant partial effect on the stock prices of manufacturing companies in the JII. In contrast, economic growth and previous period stock prices have a positive and significant impact. Simultaneously, inflation, economic development, and previous period stock prices influence stock prices in the JII. Originality/Values: These findings highlight that investors must consider various economic factors when making investment decisions.